Supporting all children to reach their potential: practitioner perspectives on creating an inclusive school environment. Issue 6 (18th August 2019) - Kendall, Lynne
ABSTRACT: This paper explores practitioner perspectives on effective inclusion within a school environment. Inclusion within school settings is more than children with a range of needs, including special educational needs (SEN) being taught together within a classroom. It is important that a school community recognises the uniqueness of each child and works together to address those individual needs, helping the child to reach their full potential. Data was gathered through interviews from fourteen members of teaching and support staff within one primary school in the North of England, identified by the Office for Standards in Education (Ofsted) as being an inclusive school. Findings report that in order to make inclusion effective for all children, practitioners acknowledged the importance of collaborative practice within the school, with outside agencies and parent partnership. A number of barriers to effective inclusion were also highlighted, including inadequate pre-service training, the national curriculum, mandatory testing at the end of key stages and school funding.